2021
DOI: 10.1093/protein/gzab017
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of multi-site nicking mutagenesis for generation of large, user-defined combinatorial libraries

Abstract: Generating combinatorial libraries of specific sets of mutations are essential for addressing protein engineering questions involving contingency in molecular evolution, epistatic relationships between mutations, as well as functional antibody and enzyme engineering. Here we present optimization of a combinatorial mutagenesis method involving template-based nicking mutagenesis, which allows for the generation of libraries with >99% coverage for tens of thousands of user-defined variants. The non-optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…To demonstrate the capability of MAGMA-seq to track potential development trajectories of multiple antibodies simultaneously, we selected three anti-S1 antibodies [29][30][31] that target Wuhan Hu-1 S1 at two distinct domains, the RBD and the NTD (Figure 2a). For each of these antibodies, mutagenic libraries theoretically comprising all possible sets of mutation between the mature and inferred universal common ancestor (UCA) were constructed using combinatorial nicking mutagenesis 32,33 and the libraries were pooled in approximately equimolar ratios and assembled into the yeast surface vector with a target of multiple barcodes per antibody variant (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the capability of MAGMA-seq to track potential development trajectories of multiple antibodies simultaneously, we selected three anti-S1 antibodies [29][30][31] that target Wuhan Hu-1 S1 at two distinct domains, the RBD and the NTD (Figure 2a). For each of these antibodies, mutagenic libraries theoretically comprising all possible sets of mutation between the mature and inferred universal common ancestor (UCA) were constructed using combinatorial nicking mutagenesis 32,33 and the libraries were pooled in approximately equimolar ratios and assembled into the yeast surface vector with a target of multiple barcodes per antibody variant (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…1). Previous data indicated that longer homology arms could improve mutagenesis efficiency [17], and that the melting temperature (T m ) of the mutagenic primer was correlated with mutagenesis efficiency [18]. We reasoned that since binding of both homology arms to the template is required for efficient mutagenesis, performance could be improved by optimizing the T m of both arms of the primer independently.…”
Section: Resultsmentioning
confidence: 99%
“…After the n/a: not available; [a] The average of the two reported independent runs of optimized multi-site NM is given (Table 1 in Ref. [49]).…”
Section: In Vivo Techniques For Saturation Mutagenesismentioning
confidence: 99%
“…Double mutations were depleted in near adjacent positions, likely because a second oligonucleotide would either not anneal properly or overwrite the mutation from the first oligonucleotide. An optimized protocol for performing multi‐site NM has recently been developed [49] . This protocol uses model‐driven oligo design to achieve >99 % coverage of a multi‐site mutagenized 32.768 membered antibody library (Table 2).…”
Section: Changing Residues: Oligo Pool‐based Multiple Site‐saturation...mentioning
confidence: 99%
See 1 more Smart Citation